The Application of Table Sugar and Coconut Water to Enhance the Growth of Post-Acclimatized Moon Orchids (Phalaenopsis Hybrid) - Ratna Nurhayati, Dewi; Sita Sari, Rika (Riviera Publishing, 2023)
Research on